2014
DOI: 10.4039/tce.2014.37
|View full text |Cite
|
Sign up to set email alerts
|

Attraction ofEpilachna dodecastigma(Coleoptera: Coccinellidae) toMomordica charantia(Cucurbitaceae) leaf volatiles

Abstract: Epilachna dodecastigma (Wiedemann) (Coleoptera: Coccinellidae) is an important herbivorous pest of bitter gourd, Momordica charantia Linnaeus (Cucurbitaceae) plant in India and Bangladesh. Volatiles were collected from undamaged bitter gourd plants, and from plants 24 and 120 hours following the initiation of continuous adult female feeding damage, and subsequently identified and quantified by gas chromatography mass spectrometry and gas chromatography flame ionisation detector analyses. Of the 24 volatiles id… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 29 publications
(17 citation statements)
references
References 31 publications
1
16
0
Order By: Relevance
“…Geranyl linalool was detected in the headspace of M. cochinchinensis leaves (Mukherjee et al., ) and S. amplexicaulis flowers, but not in the headspace of M. cochinchinensis flowers. Hence, this study confirms that variation in volatile compounds occurs between plant species, as well as between parts within a plant (Fernando & Grün, ; Tasin et al., , ; Sarkar et al., ).…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…Geranyl linalool was detected in the headspace of M. cochinchinensis leaves (Mukherjee et al., ) and S. amplexicaulis flowers, but not in the headspace of M. cochinchinensis flowers. Hence, this study confirms that variation in volatile compounds occurs between plant species, as well as between parts within a plant (Fernando & Grün, ; Tasin et al., , ; Sarkar et al., ).…”
Section: Discussionsupporting
confidence: 83%
“…Volatile blends are known to differ among plant species, qualitatively as well as quantitatively (e.g., Fernando & Grün, ; Bruce et al., ; Schoonhoven et al., ; Tasin et al., , ; Wang et al., ). 1‐Tridecanol was predominant followed by phytol in the volatiles of Momordica charantia L. (bitter gourd) plants, and geraniol, 1‐tridecanol, and phytol attracted Epilachna dodecastigma Wiedemann beetles (Sarkar et al., ). The major VOCs emitted by fruit and vines of bitter gourd have been found to contain myrtenol, ( Z )‐3‐hexenol, benzyl alcohol, 1‐penten‐3‐ol, ( Z )‐2‐pentenol, ( E )‐2‐hexenal, and cis ‐sabinol, and these volatiles elicited attraction of the fly Dacus cucurbitae (Coquillett) (Binder et al., ).…”
Section: Discussionmentioning
confidence: 99%
“…A female was considered to have made a choice in case of reaching the end of one arm, the insect was removed from the Y-tube and the choice of the insect was recorded as a positive or negative response, respectively. In contrast, a female was discarded not having made a choice within 2 min (non-responding) and was replaced by a new one (Mukherjee et al ., 2015 a ; Sarkar et al ., 2015). Each experiment with one test sample was conducted until a total of 90 naïve female insects had responded; and after testing five insects the olfactometer set-up was cleaned with petroleum ether followed by acetone, and the position of the two arms was systematically changed in order to avoid positional bias.…”
Section: Methodsmentioning
confidence: 99%
“…We did not find evidence that extracts obtained from intentionally damaged branches provoked a greater allelopathic effect in T . recurvata seed germination, but according to the PCA chemical content analysis, those extracts with intentional damage contain more trans -9-hexadecen-1-ol, cis -9-eicosen-1-ol and 1-hexadecanol; of these it has been shown that 1-hexadecanol may increase their concentration due to plant injury [ 41 ]. When herbivores feed they liberate specific enzymes that activate the host defense mechanisms [ 1 , 2 , 42 , 43 , 44 ].…”
Section: Discussionmentioning
confidence: 99%